Analysis of Initial Scientific Literacy Mastery in Elementary Schools - Ummah, Nur Fadhilah; Suryanti, Suryanti; Prahani, Binar Kurnia (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This research aims to measure and explain mastery of scientific literacy and provide several alternatives to foster mastery of scientific literacy in elementary schools, especially at SDN Tambakrejo 2. This study is quantitative research. The population of this research was all class VI of SD Negeri Tambakrejo 2 in the 2024/2025 academic year. The research sample was one class of class VI students totaling 20 people using a cluster random sampling technique, namely by randomly selecting one class as the research sample. The data collection techniques used were tests and interviews. Data analysis techniques in research use quantitative data analysis techniques with a descriptive approach. The research results showed that of the 20 students, three students had a percentage of 15% in the very low category, 12 students had a percentage of 60% in the low category, four students had a percentage of 20% in the medium category, and a percentage of 5% in the high mastery category. This research concludes that the mastery of scientific literacy of class VI students at SDN Tambakrejo 2 still needs to be improved. To develop this ability, teachers can apply contextual problem-based learning. This method, supported by an appropriate learning approach, can improve students' critical thinking abilities and problem-solving skills.